Peroral Endoscopic Myotomy in Pediatric Patients with Achalasia up to 12 Years of Age: A Pilot Study in a Single-Center Experience in Japan - Samejima, Yoshitomo; Yoshimura, Shohei; Okata, Yuichi; Sakaguchi, Hiroya; Abe, Hirofumi; Tanaka, Shinwa; Kodama, Yuzo; Bitoh, Yuko (European Journal of Pediatric Surgery, 2023)
Introduction Peroral endoscopic myotomy (POEM) is a minimally invasive endoscopic procedure for achalasia; its indication has expanded from adults to children. We aimed to evaluate the postoperative efficacy and antireflex status of POEM in young children with achalasia aged 12 years or younger.Patientsand Methods Pediatric patients with achalasia aged 18 years or younger who underwent POEM in our hospital between 2016 and 2021 were included and divided into two age groups: group A (≤ 12 years) and group B (13–18 years). The success rate (Eckardt score ≤ 3), endoscopic reflux findings, and antiacid use at 1 year postoperatively were compared between the groups.Results Ten patients (four boys and six girls; Chicago classification type I: five, type II: four, and unclassified: one) were included. Mean age and preoperative Eckardt scores in groups A (n = 4) and B (n = 6) were 9.2 ± 3.0 versus 15.6 ± 0.6 years (p = 0.001) and 5.5 ± 3.9 versus 7.2 ± 3.7 (p = 0.509), respectively, and mean operative time and myotomy length were 51.3 ± 16.6 versus 52.5 ± 13.2 minutes (p = 0.898) and 10.8 ± 4.6 versus 9.8 ± 3.2 cm (p = 0.720), respectively. The 1-year success rate was 100% in both groups. Mild esophagitis (Los Angeles classification B) was endoscopically found in one patient in each group (16.7 vs. 25.0%, p = 0.714), and antiacid use was required in three patients (group A, two; group B, one; 50.0 vs. 16.7%, p = 0.500).Conclusion The success rate of POEM within 1 year in young children with achalasia aged 12 years or younger was equal to that in adolescent patients. However, young children tended to require antiacids 1 year postoperatively; therefore, long-term follow-up is necessary.
Keywords: esophageal achalasia; gastroesophageal reflux disease; peroral endoscopic myotomy